2020
DOI: 10.2147/dddt.s244865
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synthesis and Biological Evaluations of Monocarbonyl Curcumin Inspired Pyrazole Analogues as Potential Anti-Colon Cancer Agent</p>

Abstract: The monocarbonyl analogs of curcumin (MCACs) have been widely studied for their promising antitumor activity. Pyrazole is a five-membered aromatic heterocyclic system with various bioactivities incorporated frequently in drugs. However, few of MCACs inspired pyrazole analogues were investigated. To search for more potent cytotoxic agents based on MCACs, a series of new 1,5-diaryl/heteroaryl-1,4-pentadien-3-ones inspired pyrazole moiety was synthesized and evaluated on their anti-colon cancer activities. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Similar results were reported when a diarylpentanoid, DM-1 treated in melanoma cells and EF24 in hepatocellular carcinoma cells (Liu et al, 2012;Faião-Flores et al, 2013). Besides, studies on multiple human colon cancer cell lines indicated that DAPs induced apoptosis by activating caspase-3 activity (Subramaniam et al, 2008;Selvendiran et al, 2010;Liang et al, 2017;Min et al, 2020) and reducing Bcl-2 protein (Lin et al, 2011;He et al, 2016). These findings suggest that activation of caspase-3 and downregulation of Bcl-2 in treated cells demonstrated the apoptosis-inducing ability of MS13.…”
Section: Discussionsupporting
confidence: 78%
“…Similar results were reported when a diarylpentanoid, DM-1 treated in melanoma cells and EF24 in hepatocellular carcinoma cells (Liu et al, 2012;Faião-Flores et al, 2013). Besides, studies on multiple human colon cancer cell lines indicated that DAPs induced apoptosis by activating caspase-3 activity (Subramaniam et al, 2008;Selvendiran et al, 2010;Liang et al, 2017;Min et al, 2020) and reducing Bcl-2 protein (Lin et al, 2011;He et al, 2016). These findings suggest that activation of caspase-3 and downregulation of Bcl-2 in treated cells demonstrated the apoptosis-inducing ability of MS13.…”
Section: Discussionsupporting
confidence: 78%
“…FLLL-11 which is identical to MS13 was believed to inhibit cell viability, proliferation and induce apoptosis via caspase 3 in human colorectal cancer cell lines [ 45 ]. It was reported that DAPs demonstrated anti-cancer effect through induction of apoptosis in various human colon cancer cell lines involving activation of caspase-3 [ 28 , 39 , 114 , 115 ] and down-regulation of anti-apoptotic Bcl-2 protein [ 116 , 117 ] even at a very low concentration between the range of 2.5–6.0 µM [ 45 , 117 ]. Another DAP, 1,5-bis (2-metoxyphenyl)-1,4-pentadiene-3-one (B63) was shown to induce apoptosis in human colon cancer cells via the mitochondrial apoptotic pathway which includes down-regulation of mitochondrial complexes, up-regulation of pro-apoptotic proteins-Bad and Bim, activation of caspase-3, PARP cleavage and cytochrome c release [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among asymmetric MACs synthesized, 7a , 7c , 7g, 10a , and 10g were described before in the literature. 55 , 56 …”
Section: Methodsmentioning
confidence: 99%
“…Among asymmetric MACs synthesized, 7a, 7c, 7g, 10a, and 10g were described before in the literature. 55,56 Figure 9. Physicochemical properties of compounds 7d, 7h, and 10c, in comparison with those of curcumin, colchicine, and paclitaxel.…”
Section: General Procedures For the Synthesis Of Asymmetric Macs 7a−10hmentioning
confidence: 99%
See 1 more Smart Citation